2021
DOI: 10.7150/ijbs.62929
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Smad3 protects against C-reactive protein-induced renal fibrosis and inflammation in obstructive nephropathy

Abstract: Introduction and Aims: Elevated plasma levels of C-reactive protein (CRP) are closely associated with progressive renal injury in patients with chronic kidney disease (CKD). Here, we tested a hypothesis that CRP may promote renal fibrosis and inflammation via a TGF-β/Smad3-dependent mechanism.Methods: Role and mechanisms of TGF-β/Smad3 in CRP-induced renal fibrosis and inflammation were examined in a mouse model of unilateral ureteral obstruction (UUO) induced in CRP Tg/Smad3 KO mice and in a rat tubular epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 30 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…CRP can activate Smad3 to mediate renal fibrosis directly via the CD32b-ERK/p38 MAP kinase-crosstalk pathway and indirectly through the TGF-β1-dependent mechanism 41 . This is also confirmed by deleting Smad3 to inhibit UUO-induced renal fibrosis in CRP transgenic mice 43 .…”
Section: Regulatory Role and Mechanisms Of Smad3 In Renal Fibrosismentioning
confidence: 66%
See 1 more Smart Citation
“…CRP can activate Smad3 to mediate renal fibrosis directly via the CD32b-ERK/p38 MAP kinase-crosstalk pathway and indirectly through the TGF-β1-dependent mechanism 41 . This is also confirmed by deleting Smad3 to inhibit UUO-induced renal fibrosis in CRP transgenic mice 43 .…”
Section: Regulatory Role and Mechanisms Of Smad3 In Renal Fibrosismentioning
confidence: 66%
“…Interestingly, recent studies also show that deletion of Smad3 from db/db and human CRP transgenic mice can inhibit renal inflammation by blocking MCP-1-dependent macrophage infiltration 65 . Furthermore, deficiency of Smad3 shows to exert its inhibitory effect on NF-κB-driven renal inflammation as seen in many mouse models of kidney disorders 41 , 43 . It is likely that deletion of Smad3 may suppress expression of E3 ubiquitin-protein ligases such as Smurf1/Smurf2 that target Smad2, Smad7, and TβRI for degradation.…”
Section: Regulatory Role and Mechanisms Of Smad3 In Renal Inflammationmentioning
confidence: 99%
“…Treatment with specific inhibitors SIS3 and SB431542 also demonstrated that SMAD3 and SMAD2 were jointly involved in the nontoxic concentration of OTA exacerbating ADR- or CSA-induced glomerular injury or glomerular cytotoxicity. Consistent with our study, inhibition of TGF-β1 signaling limited the progression of fibrosis in a variety of renal disease models. Therefore, inhibition of TGF-β1/SMAD signaling can alleviate CKD, suggesting that the TGF-β1/SMAD2/3 signaling pathway will be a potential target for future research on prevention and treatment of OTA poisoning and the development of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Five different cortical fields were randomly selected from each slice (magnification 200 times). The area of fibrotic lesions was expressed as the percentage of fibrotic area in the whole cortex [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%